Decision-maker characteristics and international decisions for SMEs. Issue 10 (16th November 2015) - Francioni, Barbara; Musso, Fabio; Cioppi, Marco
Abstract : Purpose: – The purpose of this paper is to explore how characteristics of decision-makers influence internationalization strategies within small and medium-sized enterprises (SMEs), with a particular focus on the strategic decision-making process (SDMP). Design/methodology/approach: – This work is based on a sample of 165 decision-makers of SMEs, using hierarchical multiple regression to examine the relationship between the dimensions studied. Findings: – The results of a regression analysis suggest that decision-makers tend to follow a more rational SDMP depending on their education level and risk attitude, and the firm's past international performance. At the same time, the political behaviour of the decision-maker emerges as a character associated with their risk attitude and need for achievement, and it is negatively influenced by age. Originality/value: – This research contributes to the growing literature on SMEs, combining the field of analysis of SDMP with that of international strategy. Moreover, unlike previous studies, which have focused on the top management team, managers, CEOs, or entrepreneurs, this study analyses the characteristics and behaviour of decision-makers.